Democracy Governance and Human Security in Nigeria: A Need for Recap - Yemi Daniel Ogundare; Yushau Sulaiman Abubakar Alfakoro (Indonesian Association for Public Administration, 2026)
The relationship between democracy and human security is often assumed to be mutually reinforcing, with democratic governance expected to promote citizens’ welfare, political freedom, and socioeconomic well-being. However, the Nigerian experience presents a significant puzzle: despite more than two decades of uninterrupted democratic rule since 1999, the country continues to experience persistent poverty, insecurity, unemployment, food insecurity, weak healthcare systems, and a decline in public trust in governance. This study investigates why democratic governance has not translated into meaningful human security outcomes in Nigeria, despite the institutional presence of democratic structures and processes. This study is anchored in Human Security Theory and adopts a qualitative case study approach. Data were obtained from semi-structured interviews, focus group discussions, and relevant secondary sources, including policy documents, journal articles, government reports and other scholarly materials. The data were analyzed thematically. The findings reveal that the relationship between democracy and human security in Nigeria is mediated by weak institutional capacity, poor governance quality, policy discontinuity, elite-driven political behavior, and inadequate implementation of development programmes. While democratic administrations have introduced various policies aimed at improving citizens’ welfare, these initiatives have produced limited results owing to governance failures and institutional weaknesses that undermine the effective delivery of public goods and services. The study argues that democracy is a necessary but insufficient condition for human security, as the benefits of democratic governance can only be realized when supported by effective institutions, accountability, policy consistency, and citizen-oriented governance practices. This study contributes to the democracy-human security debate by demonstrating that the persistence of human security challenges in Nigeria is not primarily a consequence of democracy itself, but of the weak institutional mechanisms through which democratic governance is implemented. The study recommends strengthening governance institutions, improving accountability mechanisms, ensuring policy continuity, and adopting a comprehensive human security framework that simultaneously addresses freedom from fear and want.